2016
DOI: 10.1093/gerona/glw017
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia Is Associated With Lower Skeletal Muscle Capillarization and Exercise Capacity in Older Adults

Abstract: These findings suggest that low skeletal muscle capillarization is one factor that may contribute to sarcopenia and reduced exercise capacity in older adults by limiting diffusion of substrates, oxygen, hormones, and nutrients. Strategies to prevent the aging-related decline in skeletal muscle capillarization may help to prevent or slow the progression of sarcopenia and its associated functional declines in generally healthy older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 41 publications
5
71
1
Order By: Relevance
“…Since sarcopenia is associated with lower skeletal muscle capillarization [42], the effect of baicalein on muscle capillarization was interesting; however, the effect of baicalein on muscle capillarization has not been described yet. We analysed the number of capillaries per 0.5 mm 2 muscle tissue in M. soleus (3A), M. gastrocnemius (Figure 3(b)), and M. longissimus (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 99%
“…Since sarcopenia is associated with lower skeletal muscle capillarization [42], the effect of baicalein on muscle capillarization was interesting; however, the effect of baicalein on muscle capillarization has not been described yet. We analysed the number of capillaries per 0.5 mm 2 muscle tissue in M. soleus (3A), M. gastrocnemius (Figure 3(b)), and M. longissimus (Figure 3(c)).…”
Section: Resultsmentioning
confidence: 99%
“…156 Besides the muscular force, muscular endurance is negatively associated with BMI, 157 which is also a characteristic of sarcopenia. 158 Interestingly, subcutaneous fat does not appear to induce muscle wasting to the same extent as visceral fat. Consistently, the increase in visceral and not total fat mass upregulated ubiquitin ligase, muscle RING-finger protein-1 (MuRF-1), caspase-3, and poly-ADP-ribose polymerase cleavage in muscle of rats with obesity.…”
Section: Sarcopeniamentioning
confidence: 96%
“…Similar to ageing, obesity triggers the infiltration of fat into muscle, which could be a cause of early development of sarcopenia as the intramuscular lipid droplets hinder the regeneration potential and function of skeletal muscle . Besides the muscular force, muscular endurance is negatively associated with BMI, which is also a characteristic of sarcopenia . Taken together, patients with obesity have been shown to have difficulty in performing activities of daily living and are more at risk of falls and fractures, common features of sarcopenia and ageing.…”
Section: Obesity and Age‐related Diseasesmentioning
confidence: 99%
“…Our observations suggest that skeletal muscle capillarisation may play a role in the maintenance of muscle mass and a reduction in angiogenesis may contribute to sarcopenia and physical decline in elderly people [18]. Indeed, animal studies have shown that endothelial cell apoptosis and impairment in capillary function leads to a decline in muscle mass [30].…”
Section: Discussionmentioning
confidence: 99%
“…Their release is stimulated by bone-derived cytokines as well as hypoxia, simulating bone injury. It has also been proposed that sarcopenia or muscle weakness due to ageing may be related to reduced capillary density in the muscles [18]. Levels of various angiogenic factors may decline in muscles with ageing.…”
Section: Introductionmentioning
confidence: 99%